Testing the conditional convergence hypothesis for Pakistan - Sajjad Ahmad Jan; A. R. Chaudhary (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2011)
This study investigates for the existence or non-existence of conditional convergence across the provinces of Pakistan. The annual output data from 1973 to 2000 is pooled for the four Pakistani provinces. The cross-sectional specific effects, the time specific effects, the manufacturing output, and the structural variable for aggregate supply or production shocks are used to control the different steady state levels of per capita incomes of the different provinces. The equation for conditional convergence is estimated through generalized least squares (GLS) method, after controlling for the different steady states of the provinces. The result shows that the provinces of Pakistan converge to their own respective steady states with a convergence speed of 11% per annum. At the same time manufacturing output is also statistically significant and positively affects the economic growth in the provinces. However the structural variable is not statistically significant.
Keywords: 330; Conditional Convergence; Steady State Level of Income; Gross Provincial Product (GPP); Provinces of Pakistan; Regionalentwicklung; Wirtschaftliche Konvergenz; Nationaleinkommen; Provinz; Pakistan